Brand Awareness in the Digital Era: A Study of Tokopedia Consumers in Jepara - Lusianti, Dina; Aura, Muhammad; Marka, Mira (International Journal of Law Social Sciences and Management, 2025)
Tokopedia is one of the largest e-commerce platforms in Indonesia and has played a significant role in driving the growth of the national digital economy. This study aims to analyze the influence of advertising appeal, celebrity endorsement, electronic word of mouth, and social media marketing on brand awareness among Tokopedia consumers in Jepara Regency. This research employs a quantitative approach with a sample size of 97 respondents who are Tokopedia users in Jepara Regency. The sampling technique used in this study is proportional sampling. The results of the study show that; Advertising appeal has a positive effect on brand awareness; Celebrity endorsement significantly influences brand awareness; Electronic word of mouth contributes positively to brand awareness; Social media marketing proves to be effective in improving brand awareness; and Advertising appeal, celebrity endorsement, electronic word of mouth, and social media marketing simultaneously have a positive effect on brand awareness among Tokopedia consumers in Jepara Regency.